Uji Validitas, Struktur Internal, dan Measurement Invariance pada Alat Ukur Achievement Goal Orientation - Jamaludin Jamaludin (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
AbstractAchievement goal orientation (AGO) is the goal orientation to achieve achievement. This study aims to explore information about the achievement goal orientation (AGO) measurement tool. This study combines two AGO measurements (original and revised) developed by Midgley et al (1998, 2000) based on the Manual for the patterns of adaptive learning scales (PALS). In this study only measured two of the three dimensions analyzed, namely AGO performance and AGO mastery. The sample in this study amounted to 544 people from three junior high schools in West Jakarta. Twenty-one items (10 items AGO performance and 11 items AGO mastery) were tested for validity, internal structure, and invariance measurement. The results of the validity of the CFA found that AGO performance and AGO mastery were not appropriate to measure the dimensions of AGO. Based on the results of internal structure analysis, the bifactor model is more valid and appropriate in measuring AGO performance and AGO mastery. The results of the Bifactor AGO performance analysis are divided into factors of